Obesitas dan hubungannya dengan polimorfisme gena promoter 5-HT2A, tekanan darah, profil lipid, kadar glukosa, dan malondialdehid - Pramudji Hastuti; Nur Anisah; Johan Iswara Siagian; Kautsar Prastudia Eko Binuko; Aidil Adhla (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2011)
Background: Obesity among adults has risen significantly in the world-cutting across all ages, racial and ethnic groups and gender. The 5-HT 2A receptor is crucially involved in regulation of body weight and the appetite. Disturbances in the distribution and or gene regulation of the postsynaptic 5-HT2A receptor are implicated in the pathophysiology of conditions such as obesity, coronary heart disease, high blood pressure, diabetes, stroke dan some cancers.Objective: To test the association between obesity with polymorphism of promoter -1438G→A 5-HT2A receptors gene, blood pressure, lipid profiles, levels of blood glucose and malondialdehyde (MDA).Method: This cross-sectional study included thirty six unrelated obese young people (BMI ≥ 30) recruited from populations in Yogyakarta and 36 controls with age matched with BMI ≤ 25. Statistical differences between blood pressure, lipid profiles, glucose and MDA levels were assessed by t-test and genotypes by Chi square test.Results: There were no significant difference in blood pressure lipid profile, level of glucose and MDA in obese group compared with control (p>0,05). Allele A and G frequency in obese group 25% and 75% respectively, and controls 22.2% and 77.8% respectively, and no significant difference in all two groups, but G allele had higher risk to obese than A allele.Conclusion: These data indicated G allele was mild risk factor for obesity.